Comparing modes of delivery of a combination of ion channel inhibitors for limiting secondary degeneration following partial optic nerve transection - Toomey, Lilian; Bartlett, C.A.; Gavriel, N.; McGonigle, Terence; Majimbi, Maimuna; Gopalasingam, G.; Rodger, J.; Fitzgerald, Melinda (NATURE RESEARCH, 2019)
© 2019, The Author(s).